Enhancing Cross-Cultural Training Efficacy on Expatriate Adjustment through Emotional Intelligence and Social Capital - Ely Susanto; Rokhima Rostiani (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
Cross cultural training is widely believed to make a positive contribution to expatriate adjustment. In practice, however, it is very costly and sometimes ineffective for expatriates. Therefore, there is a growing importance placed on increasing the cost effectiveness or enhancing the efficacy of crosscultural training by functioning individual expatriate’s social capital and emotional intelligence as moderating variables towards expatriate’s adjustment and performance. To do so we blend ideas drawn from social capital theory and emotional intelligence to develop the structure that underlies the logic of this paper. Thus, this paper uses social capital and emotional intelligence theories to enrich extant literature on expatriate adjustment